Ionospheric effects of the missile destruction on 9 December 2009. Issue 5 (12th May 2014) - Kozlovsky, Alexander; Shalimov, Sergey; Lukianova, Renata; Lester, Mark
Abstract We report on ionosonde and meteor radar observations made in Sodankylä Geophysical Observatory (SGO, 67°22′N, 26°38′E, Finland) on 9 December 2009, during a test launch of the Russian solid propellant military missile. Due to a technical problem, the missile was self‐destroyed around 07 UT at an ionospheric height (near 200 km altitude) over the Kola Peninsula (Russia), at a distance about 500 km to east from the observatory. Products of the explosion were spread into a large area and reached the region of SGO meteor radar observations in about 2 h (around 09 UT). After about 3 h (around 10 UT), a sporadic E layer presumably composed of the remains including long‐lived metallic (aluminum and its oxides) ions, was observed near the zenith of the SGO ionosonde. We discuss possible mechanisms accounting for transport of the remains. (1) Since the event occurred during a long‐lasting period of extremely low solar and magnetic activity, the ionospheric electric field was unlikely to play a substantial role in the transport of the remains and sporadic E layer formation. (2) The horizontal transport of the remains cannot be explained by the neutral winds based on empirical models. (3) Theoretical estimations suggest that the observed transport could be due to thermospheric turbulence.